Determination of transition length in flow through porous sand material (2009)
A transition length is normally observed when fluid flows through a conduit before laminar flow is accomplished. This work examined a situation whereby porous materials were filled into the conduit and fluid was made to flow through. An attempt was made to determine this transition length for flow of water through riverbed sand of varying porosities filled into a horizontal cylindrical pipe of diameter 0.345 x 102m with piezometric water head, set at 0.06m. The transition length was observed to be constant for the samples considered and it occurred at 0.60m from the point of entrance; nevertheless, values of pressure at this point increases with increase in porosity.